“Knowledge is ageless!" – open university in Dunaújváros (Training and Practice : Journal of Educational Sciences, 2019)
“Because knowledge is ageless ...” – it was the motto of a series of lectures aimed at retired people in February 2013 at the College of Dunaújváros. After describing the role of old-age learning, knowledge acquisition and the services built on it, in my paper, I analyse the importance of the open university of DUE, and the importance of its social engagement. I present the program, its features and its main results. I certify the existence of the local institution of old-age learning, I use student interviews and statistics. At the end of the article I outline the directions of future development.